“My drinking was way worse during the pandemic”: A qualitative analysis of contextual and individual factors impacting alcohol use during the COVID-19 pandemic - Anthony Surace; Cat Munroe; Priscilla Martinez (PLoS ONE, 2025)
Background Evidence shows that alcohol use in the United States increased during the COVID-19 pandemic. This primarily quantitative work has not examined how the unique context of the COVID-19 pandemic in the U.S. may have shaped motivations for alcohol use during this crisis. To address this knowledge gap, we conducted an analysis of qualitative data from in-depth interviews examining people’s motivations for using alcohol during the COVID-19 pandemic. Methods Participants (N = 26) were derived from those who completed all three waves of the National Alcohol Survey COVID Cohort- a longitudinal population-based survey of non-institutionalized U.S. adults. Interviews were conducted from April-July 2022 over Zoom. Interview transcripts were analyzed iteratively via codebook thematic analysis. Results Participants described how both contextual and individual level factors resulted in increased alcohol use. Contextual factors included reductions in barriers to alcohol use and increases in alcohol availability and accessibility. Individual level factors included using alcohol to regulate emotions (e.g., to alleviate boredom and as an end of day “reward”) and to celebrate reconnecting with loved ones once social distancing restrictions began to ease. Conclusions Our results suggest that environmental forces may have interacted with individuals’ emotions to shape alcohol use motivations during the COVID-19 pandemic. This work helps to contextualize quantitative research on changes in alcohol use observed during the COVID-19 pandemic. More research is needed to determine the long-term impacts of pandemic era changes in alcohol use. It is also necessary for future studies to examine how such impacts may manifest differently across the U.S. population (e.g., among racial/ethnic minority individuals).